2023
DOI: 10.1186/s12903-023-02982-4
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontically induced external apical root resorption considerations of root-filled teeth vs vital pulp teeth: a systematic review and meta-analysis

Abstract: Introduction The purpose of this systematic review was to research the difference between root-filled teeth (RFT) and vital pulp teeth (VPT) in orthodontically induced external apical root resorption (EARR) and to offer suggestions for clinicians on therapeutic sequence and timing when considering combined treatment of endodontic and orthodontic. Materials and methods An electronic search of published studies was conducted before November 2022 in P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Therefore, metabolic signals from DPSCs might play a role in triggering OIIRR during OTM. Since most orthodontic force-induced root resorption is initiated from the apex and a reduced OIIRR is observed in endodontically treated teeth 18 , our present study demonstrated for the first time that hypoxic DPSCs generated succinate, which triggers osteoclastogenesis from mBMDMs and root resorption; therefore, the OIIRR may be a defense mechanism of pulp tissues to fulfill oxygen needs during OTM.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Therefore, metabolic signals from DPSCs might play a role in triggering OIIRR during OTM. Since most orthodontic force-induced root resorption is initiated from the apex and a reduced OIIRR is observed in endodontically treated teeth 18 , our present study demonstrated for the first time that hypoxic DPSCs generated succinate, which triggers osteoclastogenesis from mBMDMs and root resorption; therefore, the OIIRR may be a defense mechanism of pulp tissues to fulfill oxygen needs during OTM.…”
Section: Discussionsupporting
confidence: 50%
“…The role of dental pulp in OIIRR has been long recognized in the dental society, since nonvital teeth after root canal therapy showed reduced OIIRR when compared to its vital counterpart 18 , 19 ; however, the role of pulp tissues in the OIIRR has not been fully uncovered. OIIRR may be rather different from inflammatory root resorption in severely traumatized teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the mechano-biology behavior not being entirely understood [ 43 , 44 , 45 , 46 , 47 ], for an intact periodontium, there are reports of a safe applied force interval of 0.5–1 N as well as a larger interval of 0.28–3.31 N [ 19 , 24 , 48 , 49 , 50 , 51 , 52 ]. It must be emphasized that the external root resorption can also be induced by a multitude of other associated factors [ 31 , 32 , 40 , 42 , 49 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. However, the subject in this study is the biomechanical behavior of orthodontic force in both an intact and reduced periodontium; thus, the discussion favors only orthodontic root resorption under ischemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…There are no identified orthodontic root resorption studies for the reduced periodontium except for our earlier one [ 2 , 41 ]. Root resorption could also be induced by other associated factors such as age, population, osteoporosis, congenital syndromes, earlier trauma, or even endodontic treatments [ 31 , 32 , 40 , 42 , 49 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%